2023
DOI: 10.3138/jvme-2022-0011
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Rubric Used for Skills-Based Assessment of Veterinary Students Performing Simulated Ovariohysterectomy on a Model

Abstract: Surgical skills are an important competency for new graduates. Simulators offer a means to train and assess veterinary students prior to their first surgical performance. A simulated ovariohysterectomy (OVH) rubric’s validity was evaluated using a framework of content evidence, internal structure evidence, and evidence of relationship with other variables, specifically subsequent live surgical performance. Clinically experienced veterinarians ( n = 13) evaluated the utility of each rubric item to collect evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Raters participated in several rater training sessions over the preceding 2 years; they agreed on the ideal student performance, acceptable variations on technique, and how to score students' errors using the rubric. A previous study reported the reliability of scores produced by the rubric and raters on this assessment; the internal consistency of scores produced by the rubric was good to excellent, and inter‐rater agreement on rubric scores and pass/fail decisions was fair 18 …”
Section: Methodsmentioning
confidence: 81%
See 4 more Smart Citations
“…Raters participated in several rater training sessions over the preceding 2 years; they agreed on the ideal student performance, acceptable variations on technique, and how to score students' errors using the rubric. A previous study reported the reliability of scores produced by the rubric and raters on this assessment; the internal consistency of scores produced by the rubric was good to excellent, and inter‐rater agreement on rubric scores and pass/fail decisions was fair 18 …”
Section: Methodsmentioning
confidence: 81%
“…Therefore, we cannot predict how quickly and to what extent student performance could rebound following a return to surgical skills training, or to what extent our data may apply to other colleges or settings. We utilized a single surgical skills rubric, which was validated in a previous study and used the same raters, who achieved fair interrater reliability 18 . Assessment of global surgical competence would require multiple assessments of a student performing a variety of surgical procedures, scored using standard, objective, and validated rubrics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations